β-carotene protects rats against bronchitis induced by cigarette smoking - 庞宝森 王辰 翁心植 唐小奈 张红玉 朱淑洁 毛燕玲 辛平 黄秀霞 张海燕 祝锦 (Chinese medical journal, 2003)
Objective To investigate the protective effects of B-carotene in rats against the development of chronic bronchitis induced by cigarette smoking.Methods Forty-two Male Wistar rats were randomly divided into three study groups: ①control (n =15), animals underwent no treatment; ②cigarette smoking (n = 15), animals developed chronic bronchitis through long-term cigarette smoking twice a day for 75 d; ③β-carotene plus cigarette smoking animals (n =12) were given 1 ml or 15 mg/kg β-carotene orally every day just before cigarette smoking. The levels of IL-6, IL-8, NO, superoxide dismutase (SOD) and lipoperoxide(LPO) in serum, bronchoalveolar lavage fluid (BALF) and lung tissue were measured and the pathological changes to lung tissue were analyzed using light microscopy.Fiesults Long-term cigarette smoking caused an obvious increase in the amount of IL-6, IL-8 and LPO and a sharp decrease in the levels of NO and SOD in smoking animals compared to controls. β-carotene intake reversed all the changes induced by smoking and alleviated the pathological changes caused by chronic bronchitis.Conclusions Quantitative oral intake of B-carotene had protective effects against chronic bronchitis induced by long-term cigarette smoking, which was associated with the increased production of NO,the clearance of some oxidative free radicals (OFR) and the alleviation of chronic inflammation.